Assessment of the impact of COVID-19 on tuberculosis care at a tertiary hospital: integrating lessons from COVID-19 learned - Téllez-Navarrete, Norma A.; Romero-Tendilla, Jesús; Morales, Alejandra; Becerril, Eduardo; Alvarado-Peña, Néstor; Salazar-Lezama, Miguel A.; Garciadiego-Fossas, Pamela; Cadena-Torres, Eliane; Chavez-Galan, Leslie; Ramón-Luing, Lucero A. (Frontiers in Public Health, 2025)
IntroductionDuring the COVID-19 pandemic outbreak in 2020 until 2023, healthcare resources dedicated to critical diseases, including respiratory conditions like Tuberculosis (TB), were significantly impacted worldwide. The Instituto Nacional de Enfermedades Respiratorias “Ismael Cosío Villegas” (INER), a leading tertiary-level hospital in Mexico City and a national reference center for respiratory diseases, was designated exclusively for COVID-19 patients during these years.MethodsThis report aims to assess the pandemic’s impact on TB care at INER and propose strategies for improving TB management by integrating lessons learned from the pandemic. TB presumptive cases were reviewed between 2016-2023, covering pre-pandemic, pandemic, and post-period; the number of diagnosis tests performed and number of attending TB patients in the emergency areas, hospitalization, or outpatient consultation were analyzed. The mortality rate of patients during hospitalization was also examined.ResultsOur analysis revealed that during the pre-pandemic period (2016-2019), around 1,000 TB patient consultations were managed annually across outpatient and inpatient settings, and it drastically declined in 2020, a trend that persisted through 2021 and 2022. Survival of TB patients was affected, and disruption in TB care resulted in a decrease in TB diagnoses during the pandemic and increased mortality rates among hospitalized patients during the post-pandemic period. In response to the challenges posed by the pandemic, INER adopted innovative strategies such as telehealth services and reinforced human resources dedicated to respiratory pathologies. These efforts and enhanced diagnostic testing have strengthened the hospital’s capacity to care for TB patients. The lessons learned during the pandemic have been pivotal in reshaping and improving the healthcare system’s approach to managing TB in a tertiary care setting.